# algebra 2

posted by .

solve the syatem using the substitution method

4x - 5y = - 3
-x + 2y = 3

• algebra 2 -

Using the substitution method means you first find one of the two variables (perhaps in terms of the other variable) and then 'substitute' this result in the other equation. If we apply it on this system we would work as follows:

1) Look at the second equation. You can easily rewrite this to:
x = 2y-3
So now you have x in terms of y

2) You now simple replace every x in the first equation with result you got from the second equation, meaning:

4x - 5y= -3
<=> 4(2y-3) - 5y = -3
<=> (8y - 12) - 5y = -3
<=> 3y = 9
<=> y = 3

3) Now that we have found that y equals 3, we can replace y with 3 in the second equation. We then find that:

x = 2y-3
<=> x = 2*3 - 3
<=> x = 3

So, the solution of this system is:
x=y=3

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### algebra

Solve using the substitution method 6x-3y=18, 6x+3y=-12
3. ### Algebra

Solve using the substitution method. 0.3x+0.2y=5,0.5x+0.4y=11
4. ### Algebra

4x+y=42 6x-5y=50 Solve using the substitution method.
5. ### Algebra

x-2y=.9 4x-3y=13.1 Solve using the substitution method.
6. ### Algebra

Solve using substitution method 3x+8y=20 x=24-7y
7. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
8. ### Algebra Help!!

solve using the substitution method. y= 5 - 3x 4x + y= 7
9. ### Algebra

If 2x + 2y = 20 & 5x - 3y = 15 Solve using the substitution method.
10. ### Algebra

solve using substitution method: 4x+5y=21 x=48-6y

More Similar Questions